Pretreatment With Bacillus cereus Preserves Against D-Galactosamine-Induced Liver Injury in a Rat Model - Li, Ya-Ting; Ye, Jian-Zhong; Lv, Long-Xian; Xu, Hong; Yang, Li-Ya; Jiang, Xian-Wan; Wu, Wen-Rui; Shi, Ding; Fang, Dai-Qiong; Bian, Xiao-Yuan; Wang, Kai-Cen; Wang, Qiang-Qiang; et al. (Frontiers in Microbiology, 2019)
Bacillus cereus (B. cereus) functions as a probiotic in animals, but the underlying mechanisms remain unclear. We aim to evaluate the protective effects and definite mechanism by which the oral administration of B. cereus prevents D-galactosamine-induced liver injury of rats. Twenty-one Sprague–Dawley rats were equally assigned to three groups (N = 7 animals per group). B. cereus ATCC11778 (2x109 colony-forming units/ml) was administered to the B. cereus group via gavage, and phosphate-buffered saline was administered to the positive control (PC) and negative control (NC) groups for 2 weeks. The PC and B. cereus groups received 1.1 g/kg D-galactosamine (D-GalN) via an intraperitoneal injection to induce liver injury. Blood, terminal ileum, liver, kidney and mesenteric lymph nodes (MLNs) were collected for histological examinations and to evaluate bacterial translocation. Liver function was also determined. Fecal samples were collected for deep sequencing of the 16S rRNA using an Illumina MiSeq platform. B. cereus significantly attenuated D-GalN-induced liver injury and improved serum alanine aminotransferase (ALT) and serum cholinesterase levels (P < 0.05 and P < 0.01, respectively). B. cereus modulated cytokine secretion, as indicated by the elevated levels of anti-inflammatory cytokine interleukin-10 (IL-10) in both the liver and plasma (P < 0.05 and P < 0.01, respectively) and substantially decreased liver levels of the cytokine IL-13 (P < 0.05). A pretreatment with B. cereus attenuated anoxygenic bacterial translocation in veins (P < 0.05) and the liver (P < 0.05) and upregulated the expression of the tight junction protein 1. The gut microbiota from the B. cereus group clustered separately from the PC group, with an increase in species of families Ruminococcaceae and Peptococcaceae and a decrease in Parabacteroides, Paraprevotella and Desulfovibrio species. The potential probiotic B. cereus attenuated liver injury by restoring the balance of the gut flora and enhancing the intestinal barrier function.